Does Pre-Survey Training Impact Knowledge of Survey Administrators and Survey Outcomes in Developing Countries? Evaluation Findings of a Training of Trainers Workshop for National AIDS and Reproductive Health Survey-Plus in Nigeria - Solomon Kolawole Oyedeji PhD; Adeniyi Francis Fagbamigbe PhD; Johnbull Sonny Ogboi MSc; Adebobola Toluwalashe Bashorun MPH; Kawu Bolakale Issa MPH; Perpetua Amida MSc; Adeniyi Ogundiran DrPH; Ezire Onoriode MSc (Global Health and Education Projects, Inc., 2013)
Background: Although, Nigeria had conducted various national surveys followed by central and state level trainings for survey administrators, prior pre-survey trainings have not been systematically evaluated to assess their impact on knowledge gain and final outcome of the survey. A central training of trainers' session was organized for master trainers on the conduct of the 2012 National AIDS and Reproductive Health Survey. Objectives: To evaluate the impact of training on the quality of conduct of a national research survey in the 36 states and the Federal Capital Territory in Nigeria. Method: A total of 185 participants consisting of State AIDS Program Coordinators, Reproductive Health Coordinators, State Laboratory Scientists, Lead Supervisors and Counselor Testers were invited from the 36 states in Nigeria and the FCT for the central training of trainers in Abuja. The training lasted 5 days and the trainees were grouped into two on the basis of behavioral epidemiology and laboratory components. Training tools such as the developed protocol, training power point slides, practical sessions such as role plays, and usage of HIV rapid test kits were utilized during the training. The facilitators were drawn from Federal Ministry of Health (FMoH), universities and research Institutions as well as Non-Governmental Organizations (NGOs). The facilitators prepared and administered 25 structured questions for the behavioral group and 28 questions for the laboratory group at the beginning of the training to assess the participants' knowledge of HIV and the survey. The same questions answered by Trainees responded to the same questions prior to the commencement and at the end of the trainings. Scores were aggregated to 100 for each test. We conducted paired t-test to determine statistically significant differences between pre-test and post-test results at 0.05 significance level and ANOVA to determine if there were differences in knowledge level among different groups. Result: The overall mean pre-test and post-test scores were 64.0% and 77.4% respectively indicating a 13.4% knowledge gain above what it was at the beginning of the training. The mean pre-test score and post-test score for the Southern states (SN) were 64.7% and 80.3% while that of the Northern states (NN) were 63.5% and 75.3% representing a knowledge gain of 15.6% and 11.8% respectively. There was statistical significant difference in the post-test scores between the two regions (p=0.001) and in knowledge gained after the training (p=0.017). Conclusions and Public Health Implications: Comparison between the pre test and post test scores at the 5-day training showed a significant gain in knowledge of participants. The survey training contributed positively to the preparation and building of knowledge needed for the conduct of 2012 NARHS-plus.